Comparison of physical and mechanical properties of traditional concrete and with recycled metal fibers (Gaceta Técnica, 2022)
The purpose of this study is to determine the physical and mechanical properties of concrete with ASTM A36 grade steel shavings, and to carry out a comparative study with traditional concrete. 36 specimens were taken as a sample and steel shavings were used at 0,6%, 1,5 and 6% as fine aggregate. The chip was obtained from the lathes of the company SMF Sagitario in the City of Lima. The research design is quasi-experimental and longitudinal; the data collection technique was observation. Inferential statistics were used to verify the hypothesis, where the results indicated that there are significant differences between traditional concrete and concrete with fine aggregate (Sig.=.000). Concluding that traditional concrete is superior to compressive and tensile strength at 7, 14 and 28 days of age
Keywords: steel slag; compressive strength; tensile strength; fine aggregate concrete; concrete mixtures